A BIM-GIS integration method in support of the assessment and 3D visualisation of flood damage to a building. Issue 2 (2nd July 2016) - Amirebrahimi, Sam; Rajabifard, Abbas; Mendis, Priyan; Ngo, Tuan
Abstract: Flood damage assessment (FDA) provides an effective basis for the flood risk management process to evaluate and treat risks. Current FDA methods, however, are ill-equipped to account for the distinctiveness of buildings in the analysis. This is mainly due to their limited input data that on the one hand requires complete building information (well-represented in building information models [BIM]) and, on the other hand, the flood information (commonly managed by geographic information systems [GIS]). While such requirements cannot be satisfied via independent use of BIM or GIS, their integration can potentially be used for this purpose. The current BIM-GIS integration methods, however, are limited or application-specific. Therefore they fall short in satisfying the micro-level FDA information requirements. This paper presents a new data model as a profile of Geography Markup Language (GML) for BIM-GIS integration to support the detailed assessment and 3D visualisation of flood damage to buildings. The model was further evaluated using a case study and found effective for this purpose.